Muscle melanisation of southern sand flathead (Platycephalus bassensis) in the Tamar Estuary, Tasmania, Australia. (January 2020) - Stocker, Clayton W.; Haddy, James; Lyle, Jeremy; Nowak, Barbara F.
Abstract: Tasmanian recreational fishers have reported the presence of dark pigmentations in the usually white fillets of southern sand flathead ( Platycephalus bassensis ), a phenomenon known as muscle melanisation. Based on histology, it is suggested that eumelanin and pheomelanin are involved in the occurrence of the phenomenon. A gross melanisation scoring system was validated through a comparison with an image analysis technique, that quantified the percentage surface area of the fillets affected by muscle melanisation. The occurrence of muscle melanisation was most severe in fish inhabiting Deceitful Cove, Tamar Estuary. This indicated that muscle melanisation in P. bassensis may be caused by yet to be identified site specific factors. No significant relationships were evident between the percentage surface area of melanised muscle with condition index, age, sex, maturation stage, fish weight, fish length and size of melano-macrophage centres in the liver or spleen. Overall, this study has provided critical information that will frame the direction and focus of future P. bassensis muscle melanisation research. Graphical abstract: Image 1 Highlights: Site specificity of phenomenon confirmed in Tamar Estuary. Eumelanin and pheomelanin both detected in P. bassensis melanised fillets. Validated gross melanisation scoring system.